Chorus acceleration of radiation belt relativistic electrons during March 2013 geomagnetic storm. Issue 5 (23rd May 2014) - Xiao, Fuliang; Yang, Chang; He, Zhaoguo; Su, Zhenpeng; Zhou, Qinghua; He, Yihua; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.; Spence, H. E.; Reeves, G. D.; Funsten, H. O.; et al.
Abstract The recent launching of Van Allen probes provides an unprecedent opportunity to investigate variations of the radiation belt relativistic electrons. During the 17–19 March 2013 storm, the Van Allen probes simultaneously detected strong chorus waves and substantial increases in fluxes of relativistic (2 − 4.5 MeV) electrons around L = 4.5. Chorus waves occurred within the lower band 0.1–0.5fce (the electron equatorial gyrofrequency), with a peak spectral density ∼10−4 nT2/Hz. Correspondingly, relativistic electron fluxes increased by a factor of 102–103 during the recovery phase compared to the main phase levels. By means of a Gaussian fit to the observed chorus spectra, the drift and bounce‐averaged diffusion coefficients are calculated and then used to solve a 2‐D Fokker‐Planck diffusion equation. Numerical simulations demonstrate that the lower‐band chorus waves indeed produce such huge enhancements in relativistic electron fluxes within 15 h, fitting well with the observation.